2010
DOI: 10.1172/jci39933
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a B cell signature associated with renal transplant tolerance in humans

Abstract: Establishing long-term allograft acceptance without the requirement for continuous immunosuppression, a condition known as allograft tolerance, is a highly desirable therapeutic goal in solid organ transplantation. Determining which recipients would benefit from withdrawal or minimization of immunosuppression would be greatly facilitated by biomarkers predictive of tolerance. In this study, we identified the largest reported cohort to our knowledge of tolerant renal transplant recipients, as defined by stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

53
715
4
23

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 624 publications
(800 citation statements)
references
References 49 publications
53
715
4
23
Order By: Relevance
“…Edemir et al 18 used a rodent model to describe gene expression patterns that support the spontaneous simultaneous activation of immune effector–related pathways and protective and immune counter‐regulatory mechanisms as a response to the allogeneic transplant. In humans, we and others have previously described a dysregulation of B cell–related genes in tolerant recipients—associated with the maintenance or expansion of transitional B cells in peripheral blood 8, 9—that elicited new avenues toward understanding the role of transitional B cells in tolerance 19, 20, 21. Differential expression profiles associated with IS treatment have been demonstrated by Erickson et al 22 in the context of transplantation in rats.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Edemir et al 18 used a rodent model to describe gene expression patterns that support the spontaneous simultaneous activation of immune effector–related pathways and protective and immune counter‐regulatory mechanisms as a response to the allogeneic transplant. In humans, we and others have previously described a dysregulation of B cell–related genes in tolerant recipients—associated with the maintenance or expansion of transitional B cells in peripheral blood 8, 9—that elicited new avenues toward understanding the role of transitional B cells in tolerance 19, 20, 21. Differential expression profiles associated with IS treatment have been demonstrated by Erickson et al 22 in the context of transplantation in rats.…”
Section: Introductionmentioning
confidence: 83%
“…A number of studies, including our own, have suggested gene expression signatures of tolerance in kidney transplantation 7, 8, 9, 11, 32 or have described differential expression of smaller gene sets 11, 33, 34. None had assessed the confounding effect of IS.…”
Section: Discussionmentioning
confidence: 99%
“…Although spontaneous immune tolerance in recipients in the case of kidney transplant is rare [81], immune tolerance to allografts can be achieved by three main mechanisms: clonal deletion, anergia and immune regulation. Hematopoietic stem cells were the first cell type assessed in patients for the induction of chimerism and subsequent allograft tolerance [82], but this approach is associated with graft versus host disease (GVHD), humoral rejection and graft loss in some cases [83].…”
Section: Strategies To Limit Renal Ischemia-reperfusion Injuries and mentioning
confidence: 99%
“…Approximately 100 cases of operational tolerance in renal transplant have been reported (Orlando et al 2010) with a denominator of many tens of thousands of total kidney transplants. There are a steadily increasing number of reports of different immune monitoring phenotypes or "signatures" that characterize tolerant recipients (Brouard et al 2005Newell and Larsen 2006;Einecke et al 2010;Newell et al 2010;Sagoo et al 2010). It may be possible to use these combined signatures to identify candidates for immunosuppression weaning.…”
Section: Planned Immunosuppression Weaningmentioning
confidence: 99%